Electrically Switchable Persistent Spin Texture in a Two‐Dimensional Hybrid Perovskite Ferroelectric. (13th March 2023) - Guo, Wuqian; Xu, Haojie; Ma, Yu; Liu, Yi; Gao, Heng; Hu, Tao; Ren, Wei; Luo, Junhua; Sun, Zhihua
Abstract: As a momentum‐independent spin configuration, persistent spin texture (PST) could avoid spin relaxation and play an advantageous role in spin lifetime. Nevertheless, manipulation of PST is a challenge due to the limited materials and ambiguous structure–property relationships. Herein, we present electrically switchable PST in a new 2D perovskite ferroelectric, (PA)2 CsPb2 Br7 (where PA is n ‐pentylammonium), which has a high Curie temperature of 349 K, evident spontaneous polarization (3.2 μC cm −2 ) and a low coercive electric field of 5.3 kV cm −1 . The combination of symmetry‐breaking in ferroelectrics and effective spin‐orbit field facilitates intrinsic PST in the bulk and monolayer structure models. Strikingly, the directions of spin texture are reversible by switching the spontaneous electric polarization. This electric switching behavior relates to the tilting of PbBr6 octahedra and the reorientation of organic PA + cations. Our studies on ferroelectric PST of 2D hybrid perovskites afford a platform for electrical spin texture manipulation. Abstract : We implement electrically switchable persistent spin texture (PST) in a 2D perovskite ferroelectric, which highlights the potential of 2D ferroelectric PST‐active materials for spin manipulation and facilitates high‐performance spintronic device application.